Depression and Sleep Quality in Restless Legs Syndrome/Willis-Ekbom Disease - Ceyhun Sayman; Murat Fatih Pul; Buse Rahime Hasırcı Bayır (Boğaziçi Tıp Dergisi, 2023)
INTRODUCTION: Restless legs syndrome (RLS)/Willis-Ekbom disease (WED) is a well-known neurological sensory motor disorder. As a result of sleep fragmentation, quality of life has effected and incidence of anxiety and depression increase. Our aim with this study is to obtain the effects of RLS/WED on sleep quality and psychiatric well-being and their relationship with disease severity. METHODS: In total, 122 RLS/WED was diagnosed with RLS/WED according to the International RLS Study Group (IRLSSG) diagnostic criteria. All partipicants's sociodemographic data form, IRLSSG severity scale, Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (EUI), and Beck Depression Inventory (BDI) were filled up by senior neurologists. Frequency of depressive symptoms, excessive daytime sleepiness, and poor sleep quality were examined. RESULTS: 122 patients (94 [77%] female and 28 [23%] male) diagnosed with primary RLS/WED according to IRLSSG criteria were included into the study. The severity level of RLS/WED in 19 (15.5%) of the patients was mild-moderate, 65 (53,2%) were severe, and 38 patients (31,2%) were very serious. BDI mean score of RLS/WED patients is 15.2+-9 and EUI mean score of RLS/WED patients is 5+-3.7. There was no statistically significant difference between the groups determined according to the severity of the disease. PSQI mean score of RLS/WED patients is 9.5+-3.8. There was statistically significant difference between the groups determined according to the severity of the dis-ease. Significant differences between the groups of RLS/WED patients were found on PSQI, especially in sleep duration, efficiency, and daytime sleep dysfunction. DISCUSSION AND CONCLUSION: Many diseases such as depression accompany with RLS/WED. Early recognition and treatment of these comorbid conditions is very important for the clinical progression of the disease.